Molecular mechanism of down-regulating adipogenic transcription factors in 3T3-L1 adipocyte cells by bioactive anti-adipogenic compounds - Guru, Ajay; Issac, Praveen Kumar; Velayutham, Manikandan; Saraswathi, N. T.; Arshad, Aziz; Arockiaraj, Jesu (Springer, 2021)
Obesity is growing at an alarming rate, which is characterized by increased adipose tissue. It increases the probability of many health complications, such as diabetes, arthritis, cardiac disease, and cancer. In modern society, with a growing population of obese patients, several individuals have increased insulin resistance. Herbal medicines are known as the oldest method of health care treatment for obesity-related secondary health issues. Several traditional medicinal plants and their effective phytoconstituents have shown anti-diabetic and anti adipogenic activity. Adipose tissue is a major site for lipid accumulation as well as the whole-body insulin sensitivity region. 3T3-L1 cell line model can achieve adipogenesis. Adipocyte characteristics features such as expression of adipocyte markers and aggregation of lipids are chemically induced in the 3T3-L1 fibroblast cell line. Differentiation of 3T3-L1 is an efficient and convenient way to obtain adipocyte like cells in experimental studies. Peroxisome proliferation activated receptor γ (PPARγ) and Cytosine-Cytosine-Adenosine Adenosine-Thymidine/Enhancer-binding protein α (CCAAT/Enhancer-binding protein α or C/EBPα) are considered to be regulating adipogenesis at the early stage, while adiponectin and fatty acid synthase (FAS) is responsible for the mature adipocyte formation. Excess accumulation of these adipose tissues and lipids leads to obesity. Thus, investigating adipose tissue development and the underlying molecular mechanism is important in the therapeutical approach. This review describes the cellular mechanism of 3T3-L1 fibroblast cells on potential anti-adipogenic herbal bioactive compounds.